The cause of gravity - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2022)
An overwhelming number of the scientists assume today that the general relativity theory describes the gravity correctly. Here, another description of gravitation is presented. This new description is based on three pillars: 1. an extended mechanical view based on Newton's equations, 2. an electromagnetic view based on Maxwell's equations, 3. a quantum physical view describing gravity as a radiation phenomenon.